(untitled) (Research, Society and Development, 2021)
Didatic sequences (DS) can be defined as a set of school activities organized, in a systematic way, around an oral or written textual genre. In this context, this work aims to build an DS with the main theme of soil chemistry and the use of syntropic agriculture for elementary school children. This work was approved and financed by PROEX-UNIFEI, being linked to the project “Semeando Cientistas” which aims to popularize science for children in socioeconomic vulnerability situations. We used the STEM methodology (Science, Technology, Engeneering and Math) and the Science, Technology and Society (STS) approach to build DS, which is divided into 9 stages and 10 classes separated by an interval week. DS presents a main project (building a vegetable garden at school) and complementary activities that seek to make children able to solve a main issue considered at work as a “dilemma”. The competencies of the National Common Curricular Base (NCCB) and the relationship between STEM methodology and STS approach were studied to promote a more contextualized teaching-learning process. In addition, it was analyzed how the elements of science, technology and society are presented in the SD.